2018
DOI: 10.1051/0004-6361/201833658
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the 13CO/C18O abundance ratio in the massive star-forming region G29.96−0.02

Abstract: Aims. Estimating molecular abundances ratios from the direct measurement of the emission of the molecules towards a variety of interstellar environments is indeed very useful to advance in our understanding of the chemical evolution of the Galaxy, and hence of the physical processes related to the chemistry. It is necessary to increase the sample of molecular clouds, located at different distances, in which the behaviour of molecular abundance ratios, such as the 13 CO/C 18 O ratio, is studied in detail. Metho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…Since the column density calculation depends on τ, a similar issue arises toward the edge of the map, mainly seen for N( 13 CO) in both regions. The global values of column density found toward this region are in agreement with other star-forming regions (Shimajiri et al 2014;Paron et al 2018;Vazzano et al 2019). Inside the H II region, no 13 CO (3−2) and C 18 O (3−2) are detected.…”
Section: Physical Properties Of the Clumpssupporting
confidence: 88%
See 1 more Smart Citation
“…Since the column density calculation depends on τ, a similar issue arises toward the edge of the map, mainly seen for N( 13 CO) in both regions. The global values of column density found toward this region are in agreement with other star-forming regions (Shimajiri et al 2014;Paron et al 2018;Vazzano et al 2019). Inside the H II region, no 13 CO (3−2) and C 18 O (3−2) are detected.…”
Section: Physical Properties Of the Clumpssupporting
confidence: 88%
“…By looking at the ratio maps, we observed that the value for this latter ratio is lower towards the densest part of the region and higher toward the edges. Unfortunately, as noted by Shimajiri et al (2014), this ratio is affected by the beam filling factor which could be as low as 0.4 as well as being nonuniform over the area due to the different structures observed (Paron et al 2018). The resolution of our observations does not allow us to come to a conclusion as to the dissociation of C 18 O towards the PDR of RCW 120.…”
Section: Dynamics Of the Regionmentioning
confidence: 67%
“…Lin et al 2016). Therefore, the behaviour of the 13 CO/C 18 O abundance ratio (hereafter X 13/18 ) across molecular clouds could be used as a tool to indirectly evaluate the degree of photodissociation in the cloud (Paron et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, N ( 13 CO) and N (C 18 O) were estimated under the LTE condition for simplicity by using equation (11) in Nishimura et al (2015), as only single transitions of the CO isotopologues are available. R 13/18 estimated under LTE and non-LTE assumptions are coincident within a factor of ∼2 in the massive star-forming region G29.96-0.02 (Paron et al 2018). In our estimation, N ( 13 CO) and N (C 18 O) are not reliably determined behind the PDR shell and near the systemic velocity (V lsr =3.7 km s −1 ).…”
Section: ρ Oph a Pdrmentioning
confidence: 66%